2005
DOI: 10.1002/jgm.735
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible polymer enhances the in vitro and in vivo transfection efficiency of HVJ envelope vector

Abstract: Cationized gelatin-conjugated HVJ-E enhanced gene transfection efficiency both in vitro and in vivo. These results suggest that low molecular weight cationized gelatin may be appropriate for complex formation with various envelope viruses, such as retrovirus, herpes virus and HIV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 52 publications
(52 reference statements)
1
24
0
Order By: Relevance
“…However, we previously showed that CG-HVJ-E is remarkably stable in 50% fresh mouse serum. Although it is unproven that HVJ is degraded by complement lysis in mouse serum, as known to be the case for retrovirus and HIV (31,32), the interaction between serum proteins and HVJ-E may contribute to reduced transfection efficacy of HVJ-E. Conjugation with CG seems to protect the surface molecules of HVJ-E from the detrimental effects of serum proteins (24). In this report, CG-HVJ-E showed a proclivity toward i.p.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…However, we previously showed that CG-HVJ-E is remarkably stable in 50% fresh mouse serum. Although it is unproven that HVJ is degraded by complement lysis in mouse serum, as known to be the case for retrovirus and HIV (31,32), the interaction between serum proteins and HVJ-E may contribute to reduced transfection efficacy of HVJ-E. Conjugation with CG seems to protect the surface molecules of HVJ-E from the detrimental effects of serum proteins (24). In this report, CG-HVJ-E showed a proclivity toward i.p.…”
Section: Discussionmentioning
confidence: 62%
“…Preparation of CG-HVJ-E/Bleomycin, Polymer-Conjugated HVJ-E, and CG/Bleomycin Cationization of gelatin was done by introducing ethylene diamine into the carboxyl groups of low molecular weight gelatin (MW = 5,000), as previously described (24), and the mole-to-mole ratio of amino groups to carboxyl groups within the gelatin was 48.7. A 5-mg amount of CG was added to 300 AL of PBS containing 3 Â 10 10 particles of HVJ-E vector containing bleomycin.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…39,41 With HVJ-E, membrane fusion occurs at the cell surface, not in endosomes. 22 The fact that gene delivery by HVJ-E is not affected by inhibitors of endocytosis 51,52 indicates that the viral genome can be directly delivered to the cytoplasm. Therefore, we theorize that IFN production by HVJ-E is also mediated by RIG-I in the cytoplasm, not by TLR3, which is present on the endosomal membrane.…”
Section: Discussionmentioning
confidence: 99%